Financial Analysis of PT. Bank Jago Tbk 2019 -2023 With Common Size and Trend Approach - Rosmayati, Siti; Apriliani, Nur Hanifah (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
Financial statement analysis is a crucial tool for evaluating a company's financial performance, helping stakeholders understand trends and stability over time. Various methods can be applied, including the common size and trend analysis approaches. This study aims to assess the financial performance of PT. Bank Jago, Tbk using a descriptive quantitative method. The findings from the common size analysis indicate that the company maintained stable financial conditions from 2021 to 2023. Meanwhile, the trend analysis reveals that revenue experienced an upward trend in 2021-2022 compared to the base year. However, the company faced financial difficulties in 2019-2020, recording losses during that period. These results highlight a financial recovery in subsequent years, reflecting an improvement in the company's performance.